2015
DOI: 10.1109/tmag.2014.2357842
|View full text |Cite
|
Sign up to set email alerts
|

Loss Analysis of Induction Motors by Considering Shrink Fitting of Stator Housings

Abstract: The losses of induction motors are analyzed using the combination of stress and electromagnetic field analyses that consider the effect of shrink fitting of stator housings. In the combined analyses, the variation in the stress effect with the angle between stress and flux vectors are taken into account using an equivalent stress. The calculated losses are compared with measured results in order to confirm the validity. It is revealed that not only the core loss, but also the primary copper loss and eddy curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Effect of shrink fitting start to diminish towards magnetic saturation. Similar observation are also reported in literature [12], [21].…”
Section: Parameter For Shrink Fitting Loss Modelsupporting
confidence: 92%
See 2 more Smart Citations
“…Effect of shrink fitting start to diminish towards magnetic saturation. Similar observation are also reported in literature [12], [21].…”
Section: Parameter For Shrink Fitting Loss Modelsupporting
confidence: 92%
“…Further, the core losses are calculated by FE post-processing and it was observed that most of the stator core losses are contributed by the yoke region (about 70 %). As shrink fitting generated stresses mainly affect the yoke region [12], the difference in the measured stator core losses is due to the increased core losses in the yoke region. Fig.…”
Section: Parameter For Shrink Fitting Loss Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The deterioration of magnetic properties during the process of manufacturing electrical machines has attracted considerable research interest in the last twenty years. The manufacturing process such as pressing [1,2], welding [3], and cutting [4] yields residual stress in electric steel laminations. Induced stress, particularly that due to the cutting of electrical steel laminations has been identified as a factor that causes severe deterioration of magnetic properties [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Energy losses incurred in making the conversion from electrical to mechanical energy can be separated into three categories (1) mechanical losses, (2) winding losses, and (3) iron losses [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%